TNF-α (−308) Gene Polymorphism and Type 2 Diabetes Mellitus in Ethiopian Diabetes Patients - Ayelign B (Dove Medical Press, 2019)
Birhanu Ayelign,1 Meaza Genetu,1 Tadelo Wondmagegn,1 Gashaw Adane,1 Markos Negash,1 Nega Berhane2 1Department of Immunology and Molecular Biology, School of Biomedical and Laboratory Science, College of Medicine and Health Science, University of Gondar, Gondar, Ethiopa; 2Institute of Biotechnology, College of Computational and Natural Science, University of Gondar, Gondar, EthiopaCorrespondence: Birhanu AyelignDepartment of Immunology and Molecular Biology, School of Biomedical and Laboratory Science, College of Medicine and Health Science, University of Gondar, Gondar, EthiopaEmail birhanuayelign42@gmail.comBackground: Type 2 diabetes mellitus (T2DM) is a metabolic disorder resulting from insulin insufficiency or function. Predisposing factors for T2DM are mainly genetic and environmental. Genetic polymorphism of cytokines like tumor necrosis factor-alpha (TNF-α) is suggestive of interference with insulin-sensitive glucose uptake and induces insulin resistance that ultimately could lead to T2DM. In this study, we assessed the effect of TNF-α (−308) G/A gene polymorphism and its association with the development of T2DM in an Ethiopian population.Methods: An institutional-based cross-sectional study was conducted on study subjects with T2DM and non-diabetic healthy controls. DNA was extracted and genotyping was carried out by using amplification refractory mutation system polymerase chain reaction. A genetic-polymorphism on TNF-α (−308) G/A with T2DM was evaluated by logistic regression and Student’s t-test. A P-value Results: In the present study, we observed a significant association between T2DM and TNF-α (−308) gene polymorphism’s GG genotype [χ2 test P = 0.005, OR (95% CI) =2.667 (1.309–5.45d8)]. In contrast, no statistically significant differences were observed in the frequencies of genotypes AA and AG (χ2 test P=0.132 and 0.067, respectively). Moreover, T2DM individuals had higher concentrations of lipid profiles for those carrying the TNF-α (−308) GG genotype as compared to the control group.Conclusion: TNF-α (−308) genetic polymorphism may be implicated in the genetic susceptibility for, as well as the development of T2DM and lipid metabolism in the Ethiopian population. Therefore, a large-scale study and early screening of TNF-α (−308) genetic polymorphism may help in early management and control of diabetes and related outcomes.Keywords: TNF-α, T2DM, North West Ethiopia